MR Imaging in Menière Disease: Is the Contact between the Vestibular Endolymphatic Space and the Oval Window a Reliable Biomarker? - Conte, G.; Caschera, L.; Calloni, S.; Barozzi, S.; Di Berardino, F.; Zanetti, D.; Scuffi, C.; Scola, E.; Sina, C.; Triulzi, F. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: No reliable MR imaging marker for the diagnosis of Menière disease has been reported. Our aim was to investigate whether the obliteration of the inferior portion of the vestibule and the contact with the stapes footplate by the vestibular endolymphatic space are reliable MR imaging markers in the diagnosis of Menière disease.MATERIALS AND METHODS: We retrospectively enrolled 49 patients, 24 affected by unilateral sudden hearing loss and 25 affected by definite Menière disease, who had undergone a 4-hour delayed 3D-FLAIR sequence. Two readers analyzed the MR images investigating whether the vestibular endolymphatic space bulged in the third inferior portion of the vestibule contacting the stapes footplate. This sign was defined as the vestibular endolymphatic space contacting the oval window.RESULTS: We analyzed 98 ears: 27 affected by Menière disease, 24 affected by sudden sensorineural hearing loss, and 47 that were healthy. The vestibular endolymphatic space contacting the oval window showed an almost perfect interobserver agreement (Cohen κ = 0.87; 95% CI, 0.69–1). The vestibular endolymphatic space contacting oval window showed the following: sensitivity = 81%, specificity = 96%, positive predictive value = 88%, and negative predictive value = 93% in differentiating Menière disease ears from other ears. The vestibular endolymphatic space contacting the oval window showed the following: sensitivity = 81%, specificity = 96%, positive predictive value = 96%, negative predictive value = 82% in differentiating Menière disease ears from sudden sensorineural hearing loss ears.CONCLUSIONS: The vestibular endolymphatic space contacting the oval window has high specificity and positive predictive value in differentiating Menière disease ears from other ears, thus resulting in a valid tool for ruling in Menière disease in patients with mimicking symptoms.AAO-HNSAmerican Academy of Otolaryngology–Head and Neck SurgeryBLBblood-labyrinthine barrierCHcochlear hydropsHChealthy controlMDMenière diseasenMDnormal in a patient with MDNPVnegative predictive valuePPVpositive predictive valueSSHLsudden sensorineural hearing lossVEHvestibular endolymphatic hydropsVESvestibular endolymphatic spaceVESCOvestibular endolymphatic space contacting the oval window